(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
A prospective comparative study was carried out to evaluate haemodynamic and recovery status using infusion of propofol-midazolam-nalbuphine and ketamine-diazepam-tramadol in surgical daycases. Fifty patients of either sex aged within 18-60 years ASA grade I or II requiring routine surgery as day-case basis under GA were selected in Dept of Anaesthesia, CMH, Dhaka during February-May 2006. Cases were randomly divided equally into two groups of 25 each. Group-A received propofolmidazolam- nalbuphine infusion and infusion of ketamine-diazepam-tramadol was used in Group- B for anaesthesia. Haemodynamic parameters, recovery status and home readiness time were monitored and recorded at 10 min intervals. The variations in heart rate, systolic and diastolic BP of both groups were found statistically insignificant (p-values: 0.0524, 0.0513 and 0.0575 respectively). Recovery scores were high in Group-A (p-0.0443) and time for home-readiness were found 242±35 (mean±SD) minutes in Group-A and 367±83 minutes in Group-B (p-0.0329). Drugs used in Group-B were found highly cost effective. It is concluded that by using ketamine, diazepam and tramadol combination (group-B), we can reduce the cost of anaesthesia, which is necessity for majority of patients in our country. On the other hand, propofol, midazolam and nalbuphine combination (group-A), a costlier regime appears suitable for the patients from affluent population. Both the regimes can be practiced with safety. Journal of BSA, Vol. 21, No. 1, January 2008 36-42